2020
DOI: 10.1007/s00586-020-06528-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predicted outcome of patients lost to follow-up after degenerative lumbar spine surgery

Abstract: Purpose The relatively large number of participants lost to follow-up (attrition) in spinal registers calls for studies that investigate the features of these individuals and their possible outcome. The aim was to explore the effect of attrition on patient-reported outcome in patients undergoing degenerative lumbar spine surgery. Three groups were studied: spinal stenosis (LSS), disc herniation (LDH) and degenerative disc disorder (DDD). Methods Patients who underwent surgery for degenerative lumbar spine cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…The yearly updating of the database and introduction of new baseline variables are also expected to increase the precision of the model on the individual level over time. Dropouts may have a tendency of worse outcome than consenters also in registers [28], so there is a possible risk of overestimating success in the model. However, this is still an unsolved question [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yearly updating of the database and introduction of new baseline variables are also expected to increase the precision of the model on the individual level over time. Dropouts may have a tendency of worse outcome than consenters also in registers [28], so there is a possible risk of overestimating success in the model. However, this is still an unsolved question [29].…”
Section: Discussionmentioning
confidence: 99%
“…A second possible cause of selection bias would be loss to follow-up. This has been assessed in a recent publication [28].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, postoperative data were missing or incomplete for 59 of 228 (25%) of the patients in the fusion group and for 45 of 144 (31%) patients in decompression group. For Swespine, Parai et al 24 reported that patients who are lost to follow-up demonstrate somewhat worse outcome than follow-up responders. This means that the true treatment effects might be lower than the values reported by our study.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of this study include a large patient material and the use of validated PROMs. 29% of the patients did not have complete data and were excluded; however, a loss of 30% have been reported to not influence the outcome in spine register studies [15], but conflicting opinions has also been reported [16].…”
Section: Discussionmentioning
confidence: 99%